The Implementation Of Act No. 42 Of 1999 On The Agreement Associated Fiduciary Guarantee Made By The Notary In Kudus - Febriyan Budi Santoso; Mohamad Rofiqi; Gunarto Gunarto (Jurnal Akta, 2018)
The purpose of this study (1) To analyze whether the fiduciary Agreement of Notary in Kudus which implemented the Act No.42 Of 1999 on Fiduciary (2) to analyze What barriers and solutions for Notary in Kudus in practicing the implementation of a credit agreement with fiduciary Agreement he made. Juridical approach method performed empirically, that is an approach which is conducted to analyze the extent to which a rule of law or the law being applied effectively.[1] Discussion of the results showed that (1) fiduciary Agreement of Notary in Kudus what is already implementing Act No.42 Of 1999 on Fiduciary (2) barriers and solutions for Notary in Kudus in practice the implementation of a credit agreement with a fiduciary warranty Agreement made.Keywords: Notary Agreement; Implementation; Agreement of Fiduciary.[1] Soerjono Soekamto 1982 Pengantar Penelitian Hukum UI Jakarta Page 52